The different effects of linseed and fish oil supplemented diets on insulin sensitivity of rabbit does during pregnancy. (June 2018) - Menchetti, L.; Canali, C.; Castellini, C.; Boiti, C.; Brecchia, G.
Abstract: This study investigates the effects of linseed (rich in ɑ-linolenic acid (ALA)) and fish oil (rich in eicosapentaenoic (EPA) and docosahexaenoic acid (DHA)) supplementation on the insulin resistance of pregnant rabbits. Two months before insemination, the rabbits (15 animals/group) were fed different diets: commercial standard (group C), supplemented with 10% extruded linseed (group L), and 3% fish oil (group FO). The L group does showed both the highest feed intake before AI (P < 0.01) and the highest body weight (BW) throughout pregnancy (P < 0.001). The L does yielded less milk than the C does (P < 0.001); however, no differences were observed in either weight or size of litter at weaning. Regardless of diet, insulin concentrations and HOMA-IR values were higher during the first half of pregnancy (P < 0.001). Nevertheless, the L does showed higher mean insulin concentrations than FO rabbits (P < 0.01) and the lowest glucose clearance (P < 0.01) during pregnancy. On the other hand, pregnant FO rabbits showed the lowest glucose concentrations (P < 0.05) and the lowest Homeostasis model assessment values for insulin resistance (HOMA-IR, P < 0.05) as well as a faster restoration of baseline glucose levels following glucose load (P < 0.001). Before and during pregnancy, the BW of the rabbits was positively related to fasting sample- and tolerance test-derived indices of insulin resistance (P < 0.05) suggesting that a high pre-pregnancy BW predisposes to gestational insulin resistance. Linseed supplementation increased BW and predisposed to insulin resistance during pregnancy; whereas, fish oil improved insulin sensitivity without significant changes in BW. Highlights: We evaluate the effects of n-3 PUFA supplementation during pregnancy in rabbit. Linseed supplementation negatively influences gestational insulin resistance. Fish oil supplementation improves insulin sensitivity. Rabbit's BW, before and during pregnancy, is related to insulin resistance indices.